Microbiological and chemical characterization of bee pollen throughout the production process in the Southwest of Buenos Aires Province (Argentina) - Fernández, Leticia A. (2020)
In order to evaluate if the different stages of bee pollen production could lead to changes in the microbiota, counts of filamentous fungi and yeast, culturable heterotrophic mesophilic bacteria, aerobic spore-forming bacteria, sulfite-reducing clostridia, enterobacteria, total and thermotolerant coliforms, and the study of human pathogenic bacteria were performed. Also, the chemical characterization was carried out. We report the analysis of 36 bee pollen samples which were obtained from different sampling points throughout the production process (collecting, freezing, drying, and cleaning) in the Southwest of Buenos Aires province, Argentina. In bee pollen samples, Escherichia coli, Salmonella sp., coagulase- positive Staphylococcus, and Clostridium perfringens were not detected. A total of 2.90 x 103 colony forming units of Bacillus cereus group were counted. Culturable heterotrophic mesophilic bacteria as well as yeasts showed the highest values and drying and freezing stages did not reduce either. Although bee pollen samples were manipulated following appropriate practices under good hygienic conditions they presented counts of filamentous fungi and yeasts higher than the Argentine Food Code tolerance while they did fit the European Codes requirements. Thus, this data offers scientific support to suggest a revision of our Code in order to establish an official method for carbohydrate content analysis and to allow higher limits for filamentous fungi and yeasts for bee pollen destined to human consumption.